Telemetering Hasil Pengukuran Curah Hujan Menggunakan Transmisi Nirkabel 433 MHz - Hudiono Hudiono; Mochammad Taufik; Ridho Hendra Yoga Perdana; Amalia Eka Rakhmania (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2021)
The line of sight (LOS) microwave communication system, especially those operating at frequencies above 10 GHz, is very susceptible to rain attenuation, particularly in tropical countries such as Indonesia. Therefore, it is essential to calculate rain attenuation estimation values as a basis for consideration in designing a line of sight microwave communication system to get stable communication. In this study, telemetering was designed to measure the rainfall intensity from a rain gauge device through a 433 MHz wireless transceiver. Measurement of rainfall intensity values via an Arduino-controlled rain gauge was transmitted directly to the monitoring room, which then processed to be displayed in graphical form in real time and can also be stored as data loggers. The rainfall telemetering device users can measure rainfall remotely and without having to wait for the rain like the rainfall manual measurement.